Looking at Spillovers in the Mirror: Making a Case for “Behavioral Spillunders” - Krpan, Dario; Galizzi, Matteo M.; Dolan, Paul (Frontiers in Psychology, 2019)
Behavioural spillovers refer to the influence that a given intervention targeting behaviour 1 exerts on a subsequent, non-targeted, behaviour 2, which may or may not be in the same domain (health, finance etc.) as one another. So, a nudge to exercise more, for example, could lead people to eat more or less, or possibly even to give more or less to charity depending on the nature of the spillover. But what if spillovers also operate backwards; that is, if the expectation of behaviour 1 influences behaviour 0 that precedes it? For example, a person may form an intention to exercise prompted by a policy intervention but overeat at present as a result. We define such a possibility as a "spillunder". In the proposed article, we critically review the few papers that we have identified through a narrative literature review which have demonstrated spillunder effects to date, and we propose a conceptual framework. Based on evidence about the human mind and behaviour from psychology and economics, we argue that spillunder effects may be more common than the limited empirical findings suggest. We propose six representative mechanisms through which the prospect of behaviour 1 may impact behaviour 0: executive functions, moral licensing and moral cleansing, emotion regulation, energization, construal level, and savouring and dread. We further discuss the policy and practical implications of spillunder effects and examine methodological issues that need to be considered when empirically testing these effects. As with our earlier paper on spillovers, we aim to motivate other behavioural scientists to research behavioural spillunders more systematically and extensively, and to prompt decision makers to consider these effects when designing behavioural interventions.